2018
DOI: 10.3928/19404921-20180810-01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pain and Sleep Quality on Falls Among Nursing Home Residents in Turkey

Abstract: The current study was conducted to detect the incidence of falls among individuals in nursing homes, as well as the impact of pain and sleep quality on falls. The sample for this cross-sectional study comprised 291 older adults. Pain was assessed using the Geriatric Pain Measure and insomnia was assessed using the Insomnia Severity Index. Incidence of falls within the past 1 year was 40.9%. Risk factors for falling were determined using logistic regression analysis. Based on the analysis, being single (odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
4
0
3
Order By: Relevance
“…Investigators in the former study also found that older adults with moderate insomnia (symptoms one to five nights per week) were 47% more likely to fall within 6 months, and those with severe insomnia (symptoms at least six nights per week) were 86% more likely to fall within the same time period (Avidan et al, 2005). Two other studies found no association between insomnia and falls, one measured by the Insomnia Severity Index and the other measuring sleep latency by PSG ( p = 0.21 and p = 0.93, respectively) (Altintas et al, 2018; Batchelor et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Investigators in the former study also found that older adults with moderate insomnia (symptoms one to five nights per week) were 47% more likely to fall within 6 months, and those with severe insomnia (symptoms at least six nights per week) were 86% more likely to fall within the same time period (Avidan et al, 2005). Two other studies found no association between insomnia and falls, one measured by the Insomnia Severity Index and the other measuring sleep latency by PSG ( p = 0.21 and p = 0.93, respectively) (Altintas et al, 2018; Batchelor et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
“…Five studies examined the relationship of insomnia with falls (quality range 6–9). All studies used a different instrument for insomnia: Insomnia Severity Index (Altintas et al, 2018), PSG (Batchelor et al, 2014), Nottingham Health Profile (Pereira et al, 2013), CMS Minimum Data Set (Avidan et al, 2005), and dichotomous yes/no self‐report of insomnia (Koski et al, 1998). Three of the studies found an association, with the greatest association found in a self‐report of insomnia and associated with a four‐fold increase (95% CI 1.70–9.79) in the risk of falls resulting in major injuries (e.g., fractures or intracranial injuries) in independent older adults (Koski et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, prior research has noted that there was an increased risk of falling associated with opioid use (Daoust et al, 2018;Hunnicutt et al, 2018; Machado-Duque, Castaño-Montoya, Medina-Morales, Castro-Rodr ıguez, & Gonza´lez-Montoya, 2018), or in one study of community-dwelling older men, there was no noted association between opioid use and falling (Krebs et al, 2016). These inconsistencies may be due to whether or not the individual was naı¨ve to the drug, whether an opioid was combined with other psychoactive medications, and/or whether or not there were other risk factors for falls such as orthostatic hypotension, vision problems, pain, or altered balance (Altintas, Aslan, Sısman, & Kesgin, 2018;Musich, Wang, Slindee, Saphire, & Wicker, 2018). Although opioid use may be associated with the risk of falls, pain is likewise associated with falls due to the impact it can have on mobility and balance (Altintas et al, 2018;Picorelli, Hatton, Gane, & Smith, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies may be due to whether or not the individual was naı¨ve to the drug, whether an opioid was combined with other psychoactive medications, and/or whether or not there were other risk factors for falls such as orthostatic hypotension, vision problems, pain, or altered balance (Altintas, Aslan, Sısman, & Kesgin, 2018;Musich, Wang, Slindee, Saphire, & Wicker, 2018). Although opioid use may be associated with the risk of falls, pain is likewise associated with falls due to the impact it can have on mobility and balance (Altintas et al, 2018;Picorelli, Hatton, Gane, & Smith, 2018). It is possible, therefore, that the reason for the decreased risk of falling with opioid use in this study may be due to appropriate use of these drugs as a way in which to relieve pain and thereby optimize function.…”
Section: Discussionmentioning
confidence: 99%
“…Bu risk etmenleri arasında belirtilmeyen uyku bozukluklarının yaşlılarda düşme ile ilişkisi, son zamanlarda çalışılmaya başlanmıştır. [4][5][6][7] Uyku düzenindeki değişiklikler yaşlanma sürecinin doğal bir parçası olarak kabul edilmekte, yaşlılık döneminde uyku sorunlarının arttığı belirtilmektedir. Yaşla birlikte oluşan değişiklikler gece uyku süresinde ve yavaş dalga uykusunda azalmayı; gündüz uyku süresinde, gece uyanma sayısında, gece uyanık geçirilen sürede artışı içermektedir.…”
Section: Introductionunclassified